2021
DOI: 10.1016/j.jstrokecerebrovasdis.2020.105463
|View full text |Cite
|
Sign up to set email alerts
|

Large Artery Atherosclerotic Clots are Larger than Clots of other Stroke Etiologies and have Poorer Recanalization rates

Abstract: Objectives: There is a paucity of knowledge in the literature relating to the extent of clot burden and stroke etiology. In this study, we measured the Extracted Clot Area (ECA) retrieved during endovascular treatment (EVT) and investigated relationships with suspected etiology, administration of intravenous thrombolysis and recanalization. Materials and Methods: As part of the multi-institutional RESTORE registry, the ECA retrieved during mechanical thrombectomy was quantified using ImageJ. The effect of stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…1b). Median RBCs composition was 45 % for bridging-therapy and 44 % for MTalone clots (H1 = 0.018, P = 0.895); median FIB composition was 30 [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]% for bridging-therapy and 29 % for MT alone (H1 = 0.552, P = 0.458); median PTL composition was 16 % for bridging-therapy and 17 [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]% for MT alone (H1 = 0.014, P = 0.905). Further analysis was then performed combining size and histological composition (Fig.…”
Section: Analysis Of Extracted Clot Areamentioning
confidence: 99%
“…1b). Median RBCs composition was 45 % for bridging-therapy and 44 % for MTalone clots (H1 = 0.018, P = 0.895); median FIB composition was 30 [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]% for bridging-therapy and 29 % for MT alone (H1 = 0.552, P = 0.458); median PTL composition was 16 % for bridging-therapy and 17 [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]% for MT alone (H1 = 0.014, P = 0.905). Further analysis was then performed combining size and histological composition (Fig.…”
Section: Analysis Of Extracted Clot Areamentioning
confidence: 99%
“…Two recent studies have shown that cardioembolic and cryptogenic clots have a smaller ECA and higher fibrin and platelets/other content compared to LAA clots which are larger and associated with a RBC-rich composition. 10,14 In our cohort, the majority of 'white' We acknowledge that there are also other components in the platelets/other-rich areas identified by MSB so we performed immunohistochemistry to distinguish between platelets and platelet-related factors such as vWF. 15 The high expression of CD42b and vWF in our 'white' clots highlights their critical role in 'white' clots formation.…”
Section: Discussionmentioning
confidence: 99%
“…ImageJ software ((https://imagej.nih.gov/ij/) was utilized to measure total extracted clot area (ECA) of each clot using the gross image of the clot as previously described. 9,10 First the scale was set and then the polygon tool was used to draw a region of interest around a fragment of the clot, and the area of that fragment was measured individually. The total extracted clot area for each case is defined as the sum of the clot area from all clot fragments within a case.…”
Section: Clot Histology and Extracted Clot Area Analysismentioning
confidence: 99%
“…However, our findings also show that smaller clots were not associated with better recanalization outcome or lower number of passes, which could be related to clot properties and composition, since it has been demonstrated that small, difficult to remove clots are more platelet rich and contain more highly organised fibrin regions. 19,20 It has been demonstrated that administration of rtPA before mechanical thrombectomy reduces clot size. 21 The present study demonstrates the correlation between clot length on CTA/NCCT and area of extracted clot was slightly stronger for the cohort of patients that directly underwent mechanical thrombectomy compared to the patients pre-treated with rtPA.…”
Section: Discussionmentioning
confidence: 99%